2014
DOI: 10.1002/ppap.201400082
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Physicochemical Properties and Biological Effects of Water Activated by Non‐thermal Plasma Above and Beneath the Water Surface

Abstract: A direct current atmospheric pressure cold plasma microjet (PMJ) was used to produce plasma activated water (PAW) in two generation modes above (PAW-A) and beneath (PAW-B) the water surface. The physicochemical characteristics and biological effects of them were measured respectively. Results showed that PAW-B exhibited stronger disinfection efficiency than PAW-A, which was associated with ORP and conductivity, but not pH value, temperature, H 2 O 2 , NO 3 À or NO 2 À . Furthermore, the cell membrane integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
126
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 56 publications
10
126
1
Order By: Relevance
“…The value increased to 350 and 450 μS/cm after 10 and 20 min plasma activation, respectively. The result was consistent with our previous work [36], demonstrating that much active ions were generated in the PAW, which may be various ROS and other reactive species, playing important roles in the inactivation process.…”
Section: Evaluation Of Physicochemical Properties Of Pawsupporting
confidence: 94%
See 4 more Smart Citations
“…The value increased to 350 and 450 μS/cm after 10 and 20 min plasma activation, respectively. The result was consistent with our previous work [36], demonstrating that much active ions were generated in the PAW, which may be various ROS and other reactive species, playing important roles in the inactivation process.…”
Section: Evaluation Of Physicochemical Properties Of Pawsupporting
confidence: 94%
“…The result indicated that a large amount of ROS was generated in PAW, which was consistent with our previous publications [35,36].…”
Section: Evaluation Of Physicochemical Properties Of Pawsupporting
confidence: 93%
See 3 more Smart Citations